2016
DOI: 10.1080/14786419.2016.1185719
|View full text |Cite
|
Sign up to set email alerts
|

Two new flavans from the trunk and leaves of Horsfieldia glabra

Abstract: Two new flavans, (2R, 4R)-4'-hydroxy-3',5'-methyl-6,7-methylenedioxy-4-O-2'-cycloflavan (1), and (2R, 4R)-4'-hydroxy-3'-methyl-6,7-methylenedioxy-4-O-2'-cycloflavan (2), along with six known compounds were isolated from the trunk and leaves of Horsfieldia glabra. Their structures were elucidated by means of extensive spectroscopic analysis. Compounds 1 and 2, together with 4-7 were assessed for their cytotoxicity against five human cancer cell lines (HL-60, SMMC-7721, A-549, MCF-7 and SW-480), and the result s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…On the basis of the above evidence, the planar structure of compound 2 was elucidated as 5-methoxy-6,7-methylenedioxy-4-O-2 -cycloflavan and considered as an unprecedented natural product. This spectroscopic data of compound 2 is somewhat similar to the literature values for the known 4-O-2 -cycloflavan core structures, possessing a different substitution pattern in aromatic A-and B-rings [7,13,14].…”
Section: Structure Elucidationsupporting
confidence: 88%
See 3 more Smart Citations
“…On the basis of the above evidence, the planar structure of compound 2 was elucidated as 5-methoxy-6,7-methylenedioxy-4-O-2 -cycloflavan and considered as an unprecedented natural product. This spectroscopic data of compound 2 is somewhat similar to the literature values for the known 4-O-2 -cycloflavan core structures, possessing a different substitution pattern in aromatic A-and B-rings [7,13,14].…”
Section: Structure Elucidationsupporting
confidence: 88%
“…The coupling constant of anomeric proton J = 7.80 Hz indicated that the sugar was β-oriented. The 1 H and 13 C NMR spectroscopic data of aglycone of 9 were comparable with the literature values for the irilin A [17,18]. The only difference was occurred on C-2 , where OH group of irilin A was replaced by glucopyranosyl in 9.…”
Section: Structure Elucidationsupporting
confidence: 83%
See 2 more Smart Citations
“…So far, H. amygdalina is reported on fatty acid ingredients (Hu et al. 2010 ; Xue and Fang 2012 ; Peng 2017 ), seed propagation (Hu et al. 2011 ), leaf traits variation (Hu et al.…”
mentioning
confidence: 99%